TAMPIL MODIS DENGAN TOBACCO REJECT TEES - Falakh, Fajrul; Fitriyanto, Bagus; S P, Ramandhani Dwi; Rahmansyah, Hanif (Program Kreativitas Mahasiswa - Kewirausahaan, 2013)
Smoking issue has become a major problem which need to adressed seriously by the Government, especially in Indonesia because smoking have killed millions of Indonesia children each years. The increase of smoking prevalence occurred in the age group15-24 years, from17.3% (2007) to 18.6% or increase almost 10 % in 3 years. The increase also occurred in the productive age group, that 25-34 years from 29.0% (2007) to 31.1% (2010). From these data it can be seen that most of teenagers are smoking. Adolescence is a period where a person wants to look fashionable. T-shirt is one of fashion trend which is much demand by teenagers. Above information make us innovate to open a business that also has a contribution in the control of smokers in Indonesia. We propose the effort of making T-shirts "TOBACCOREJECT TEES" which contains the message to quit smoking as well as smoking prevention messages. In the process we formed a partnership with Central Java Provincial Health Office, Store Entrepreneurship Diponegoro University School of Public Health and Keboe Chloth Distro Store. During the marketing process shirt "TOBACCO REJECT TEES" get very enthusiastic response from consumers. During the marketingt-shirts "TOBACCO REJECT TEES" has sold more than 136 pieces of T-shirts with a profit of Rp. 25.000/pcs.Key Words: Smoking, T-Shirt, Tobacco Reject Tees